Tinjauan atas kebijakan sektor perkayuan dan kebijakan terkait lainnya - Resosudarmo, I.A.P. (Yayasan Obor Indonesia, 2003)
The forests of Indonesia have been a major source of foreign exchange and have provided substantial employment opportunities. But evidence indicates that commercial forest harvests in Indonesia have been carried out in an economically unsustainable manner. The dramatic economic and political changes in Indonesia in 1997-99 have potentially increased pressures on remaining timber resources, and the economic crisis and national leadership transition have given rise to demands for substantial changes in the management of forests. It is therefore timely to review commercial timber activities and policies to date. This paper reviews commercial forest practices and national forestry policies that affect the commercial timber sector, along with contributing factors outside the forestry sector that may have affected commercial forest practices. It finds that existing policies are insufficient to achieve sustainable management, or are ineffectively enforced. At the same time, current conditions offer an opportunity to carry out important policy changes in relation to the commercial timber sector. A preliminary analysis of these changes shows the timber sector is subject to greater potential pressures than ever before, but that there are also possibilities for important policy improvements.